PROGRAMA PARA ELABORACIÓN DE PROYECTOS DE BOMBEO FOTOVOLTAICO, CASO ISLA TAQUILE - PUNO - Espinoza Paredes, Rafael (1999)
The present article is about a program, witch is a powerful tool to help persons who need to make calculations of costs and to determine the size of many equipment and the quantities of pertinent materials for a project fulfillment of water pump with fotovoltaic energy. This program is easy to operate, and it shows a Menu with Entrance of data. Presentation of results, Print of results, Quit (Fig. 2). This program is based on the case of Taquile’s Island-Puno (pump of 24 m3/day and 200 m of total height) in order to determinate the size of fotovoltaic pump project, demonstrating the utility of the program.